ANALISIS DETERMINAN INTENSITAS ENERGI DI INDONESIA - Ilhaq, Muhammad Syahgar; Syafitri , Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to analyze the factors that influence energy intensity in Indonesia. The method used is quantitative by using Vector Autoregressive (VAR) or Vector Error Correction Model (VECM) analysis to analyze the effect of economic variables on energy intensity. The data used is in the form of time series data, data obtained from the World Bank (2021), the Energy Information Administration (EIA) and the Central Bureau of Statistics (BPS). The data observed in 1981-2021 is 40 years. The results of this study are per capita income and openness trade have a negative effect both long term and short term on energy intensity. Meanwhile, energy prices, population density, and foreign direct investment have positive long-term and short-term effects on energy intensity. the role of renewable technology and alternative energy is the biggest influence in reducing energy intensity figures in supporting economic development and a sustainable economy. With a targeted reduction of 1% in energy intensity figures every year. It is hoped that this research will help the Indonesian government in making decisions and making policies so that it can contribute to reducing energy intensity in Indonesia.